THE STRUCTURE AND FORMULA OF GERONG LYRICS IN THE PRAMBANANRAMAYANA BALLET - Untoro, Ratun; Adi, Ida Rochanib; Ahimsa, Heddy Shri (LITERA, 2017)
Abstract Gerong lyrics as the only orality in the Prambanan Ramayana ballet no longer present the story of Rama in its entirety. Although most gerong lyrics contain the scenes, the singers are not always fixated on the lyrics, but prioritize the tones of the chants. This study aims to reveal the structure and formula of gerong chants in the Prambanan Ramayana ballet. It used Levi-Strauss’ structuralism theory and Albert Lord’s formula theory and employed the qualitative descriptive method. The data were gerong lyrics and their chanting and various supporting orality elements. The results of the study show that the structure in the form of geronginter-lyric relation does not show the Ramayana story plot. In addition, a gerong chant formula is found. The chant formula becomes one of the developments of Lord’s formula theory giving priority to the formula of the oral lyrics. Keywords: Ramayana Ballet, structuralism, formula, gerong, chants